ANALISIS PEMBIAYAAN KREDIT PEMILIKAN RUMAH SYARIAH BAGI NASABAH BERPENGHASILAN RENDAH (Studi Kasus Di Bank Syariah Mandiri Kantor Cabang Pembantu Bogor Pomad) - Hilal Luddin; Tubagus Rifqy Thantawi; Azizah Mursyidah (SAHID BANKING JOURNAL, 2022)
The background of this research is the primary need in the form of a house, but until now it has not been fulfilled. Houses are very difficult to obtain for low-income people, even though there are already many financial institutions that can make it happen in fulfilling housing needs for low-income people. There are limitations set by financial institutions, one of which is a limit on the applicant's income, which adds to the difficulties mentioned above. Therefore, this problem is interesting to study, with the existence of a research problem formulation, namely how to analyze the financing of Sharia House Ownership Credit (KPR Syariah) for low-income customers (with case studies at Sharia Bank Bogor Pomad Mandiri Sub-Branch Offices or BSM KCP Bogor Pomad) . This research is a research field with qualitative methods of primary data, secondary data and interviews. The process of data analysis in this study uses descriptive analysis